ANALISIS KEBIJAKAN PEMERINTAH PUSAT DALAM RANGKA PENGEMBANGAN KUALITAS TENAGA BIDAN DI DINAS KESEHATAN KABUPATEN MINAHASA SELATAN - Putrinesia - Ruindungan; Mardiani Gina Hartoyo; Windy Tumuwe (J-KESMAS: Jurnal Kesehatan Masyarakat, 2022)
To analyze the central government policy in order to develop the quality of midwives in Health Office of South Minahasa District. Research Method: This research uses qualitative research method. The subjects of this research are government officials in South Minahasa District, Health Office, professional organization, and midwives in South Minahasa District Health Office. Data collecting method is in-depth interview. Research Results: Actors who play their role in the implementation of policies in accordance with their respective duties and functions; The context of the implementation of this policy refers to the presence of midwives in the region and is also influenced by political factors, namely improving the quality of human resources is the mission of bupati and vice regent elected and has been used as development mission of South Minahasa District and economic factors which is lack of budget provided For the implementation of quality development activities for midwives, and also influenced by the context of decentralization. This policy is useful in improving and developing the quality of midwives. The implementation process is top down from central to local government. Conclusion: The implementation of the midwives quality development policy needs to be implemented in an effort to improve the performance of midwives, either through training or further education.